Higher learning student perceptions of classroom incivility - Nur Farzana Mohamad Nahar; Ida Rosnita Ismail (Penerbit Universiti Kebangsaan Malaysia, 2023)
Being aware of and addressing incivility in educational settings is important not only for providing a positive learning environment but also for shaping the student’s behaviour once they enter the workplace. Thus, this study investigated the phenomenon of classroom incivility through the eyes of undergraduate students. The sample consisted of 120 undergraduate students from a public higher educational institution in Klang Valley, Malaysia. The data were analysed using descriptive analysis in Statistical Package for Social Sciences version 21 (SPSS v21). The findings of this study provide useful information to organizations, faculty members, and administrators about the uncivil behaviour that occurs in educational settings. The findings have implications for how faculty and administrators establish policies to guide students towards appropriate behaviour. Some initiatives that can be implemented to reduce classroom incivility include (a) establishing a code of conduct in the classroom outlining acceptable and unacceptable behaviours in the classroom, (b) addressing uncivil behaviours as soon as it begins, and (c) all university members must model good behaviour.